2018
DOI: 10.1002/mana.201600442
|View full text |Cite
|
Sign up to set email alerts
|

On the classification of contact metric ‐spaces via tangent hyperquadric bundles

Abstract: We classify locally the contact metric (k,μ)‐spaces whose Boeckx invariant is ⩽−1 as tangent hyperquadric bundles of Lorentzian space forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In the case I < −1, we obtain a new homogeneous representation of the contact metric (κ, µ) manfolds M with I M < −1, different from the Lie group representation furnished by Boeckx. Actually these models can be geometrically interpreted also as tangent hyperquadric bundle over Lorentzian space forms, as showed in [17].…”
Section: Now We Consider the Natural Decomposition Ofmentioning
confidence: 98%
“…In the case I < −1, we obtain a new homogeneous representation of the contact metric (κ, µ) manfolds M with I M < −1, different from the Lie group representation furnished by Boeckx. Actually these models can be geometrically interpreted also as tangent hyperquadric bundle over Lorentzian space forms, as showed in [17].…”
Section: Now We Consider the Natural Decomposition Ofmentioning
confidence: 98%
“…125-126). More recently, E. Loiudice and A. Lotta [93] showed that the tangent hyperquadric bundles T −1 M over Lorentzian space forms (M, g) of constant curvature c different from −1, equipped with a strictly pseudoconvex CR structure, also provide non equivalent examples. For these space, the formula for the Boeckx invariant changes as follows:…”
mentioning
confidence: 99%